Impact of daylight savings time on spontaneous pregnancy loss in in vitro fertilization patients. (28th May 2017) - Liu, Constance; Politch, Joseph A.; Cullerton, Evan; Go, Kathryn; Pang, Samuel; Kuohung, Wendy
ABSTRACT: Transition into daylight savings time (DST) has studied negative impacts on health, but little is known regarding impact on fertility. This retrospective cohort study evaluates DST impact on pregnancy and pregnancy loss rates in 1, 654 autologous in vitro fertilization cycles (2009 to 2012). Study groups were identified based on the relationship of DST to embryo transfer. Pregnancy rates were similar in Spring and Fall (41.4%, 42.2%). Pregnancy loss rates were also comparable between Spring and Fall (15.5%, 17.1%), but rates of loss were significantly higher in Spring when DST occurred after embryo transfer (24.3%). Loss was marked in patients with a history of prior spontaneous pregnancy loss (60.5%).